AB0131 Lupus monocyte-derived dendritic cells treated with 1a, 25-dihydroxyvitamin d3 and dexamethasone are tolerogenic and induce il-10 producing regulatory t cells. (23rd January 2014) - Wu, H. J.; Luk, T. W.; Lam, K. Y.; Lau, C. S.; Chan, A.; Mok, M. Y.
Abstract : Background: The pathogenesis of systemic lupus erythematosus (SLE) is characterized by dysregulated dendritic cells (DCs) with over-production of type I interferon and hyperactive adaptive immune response. Clinical benefits of tolerogenic DCs have recently been shown in some murine models of immune mediated diseases. Objectives: To examine if alternatively activated DCs (aaDCs) derived from SLE patients possess tolerogenic properties and to delineate the underlying mechanisms. Methods: Lupus and healthy control aaDCs were generated by treating monocyte derived DCs using combination of 1α, 25-Dihydroxyvitamin D3 (vitD3) and dexamethasone followed by maturation by lipopolysaccharide (LPS). These aaDCs were examined for phenotype and tolerogenic functions compared with LPS-matured DCs (matDCs). Activation markers and intracellular cytokine expression of T cells and/or DCs were measured by flow cytometry. ELISA was used to measure cytokine levels in supernatant. Western blot was performed for detection of RelB protein expression. Results: Compared with matDCs, lupus aaDCs displayed semi-mature phenotype with low level of expression of co-stimulatory molecules and maturation markers (CD83, CD40), that remained stable despite challenge by CD40L, CpG-DNA and SLE serum. These aaDCs also possessed tolerogenic phenotype with suppressive effect on allogeneic T cell activation (CD25 and CD69 expression) and proliferation comparable to normal aaDCs. Lupus and normal aaDCs were shown to polarize normal and lupus naïve CD45RA+ T cells into T effector cells that were characterized by production of high level of IL-10, expression of Foxp3 mRNA and antigen-nonspecific suppressive effect on allogeneic third-party T cells. On the other hand, lupus and normal aaDCs skewed memory CD45RO+ T cells to less inflammatory phenotype with reduced expression of IFN-γ and IL-17. Although aaDCs displayed a cytokine profile of IL-12 lo IL-10 hi, addition of neutralizing anti-IL-12 and exogenous IL-10 to culture conditions did not reverse the suppressive effect of aaDCs on activation and proliferation of allogeneic T cells, suggesting their tolerogenicity cannot be accounted by cytokine imbalance between IL-12 and IL-10. On the other hand, aaDCs were found to express reduced level of RelB, a transcription factor regulating DC differentiation and maturation. Conclusions: Lupus aaDCs demonstrated tolerogenic properties with induction of IL-10 producing T cells that have regulatory functions. Reduced expression of RelB in aaDCs may be the underlying mechanism for their tolerogenicity. Disclosure of Interest: None Declared